(untitled) (XXI Century. Spanish Literature and Culture, 2020)
Epps, Bradley y Kakoudaki, Despina eds. All About Almodóvar: A Passion for Cinema. Minneapolis, London: University of Minnesota Press, 2009. 496 páginas. Di Francesco, Maria. Feminine Agency and Transgression in Post Franco Spain: Generational Becoming in the Narratives of Carme Riera, Cristina Fernández Cubas and Mercedes Abad. Newark, Del.: Juan de la Cuesta, 2008. 217 páginas. Grohmann, Alexis y Steenmeijer, Maarten (eds.). Allí donde uno diría que ya no puede haber nada. Tu rostro mañana, de Javier Marías. Ámsterdam/New York: Rodopi, 2009.